The Teacher's Efforts in Improving Students' Interest in Learning through Interactive Learning Strategies - Saifudin Saifudin; Mispani Mispani; Dedi Setiawan (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2024)
This research is focused on the efforts by teachers of Akidah Akhlak in subjects’ interest in learning through interactive learning strategies in senior high school Ma’arif 06 of Seputih Raman Lampung Tengah. Which become the factor of inhibition and support in improving student's learning interest. This research is conducted by using field research approach (field researd) which is qualitative that implemented in junior high school Muhammadiyah of Kalirejo. Date collection is done by using interview, observation and documentation. Date analysis in this research by way of data reduction, data presentation, and conclusing drawing / verification. Testing the validity of the data obtained in this study by triangulation of sources, member check and improve persistence / keajegan observations. The results showed that teachers have eight efforts to increase students’ interest learning in senior high school Ma’arif 06 of Seputih Raman Lampung Tengah So that students become interested and enthusiastic in following the Akidah Akhalak learning. In addition there are several factors that hinder teachers in improving student learning interest such as lack of existing facilities and infrastructure, lack of supervision from parents to their children when at home, and not terancangnya learning system in accordance with learning objectives. Factors that support teachers in improving the interest of learning suiswa is the LCD that allows teachers to deliver material, the religious school environment helps pie teachers in improving student learning interest. Based on the results of the study of eight attempts made there is a dominant that gives an assessment of this is done because by providing value from the work of students will spur interest in learning. But the need to create competition and cooperation among students to spur their learning spirit. Keywords: Students Moral, Religious Education Learning